An experimental investigation of the stability of a fibre embedded in a soft gel - Ganesan, Priyadharshini (Nanyang Technological University, 2024)
This Final Year Project aims to experimentally investigate how the stability of fibres embedded in a soft gel is affected by the stiffness of the soft gel. The student conducted a series of experiments to test the stability by fabricating soft gels of various stiffness and fibres using easily obtainable household items and testing the buckling of the fibre when subjected to axial compressive loads. From the experimental results, the critical buckling load as well as the buckling shapes for the fibres embedded in different concentrations of soft gel was obtained and analysed.